Seed Priming Application to Improve the Physiological Quality of True Shallot Seed (TSS) - Andayani, Retno Dwi; Sumarji, Sumarji; Rahmatika, Widyana (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.41, 2021)
Shallots are one of vegetable that can be cultivated with bulb or seeds. Shallot seeds better known as True Shallot Seed (TSS). Shallot cultivation using TSS still encounters several obstacles including low physiological quality of seeds. Physiological quality of seed can be improved by seed priming. One of popular natural seed priming is coconut water. The goal of this experiment was to determinate the best application of seed priming to improve TSS physiological quality. This experiment use factorial completely randomized design with 3 replications. First factor is 3 kind of soaking liquid (water, warm water dan coconut water). Second factor is soaking time (1 hour, 6 hour, 12 hour, 18 hour dan 24 hour). TSS used in this experient was Tisula. The result showed that soaking TSS in coconut water for minimal 18 hours has been shown to improve seed physiological quality.